No smoking no vaping campaign TVC animation - Abdul Basir, Muhammad Khairul Aiman (Universiti Teknologi MARA, Perak, 2023)
Nowadays people do not really care and takeabout the issue pertaining to the disadvantage of smoking and vaping even lightly. There is a lot of awareness about it like images on the effect of smoking on the cigarettes box, poster, billboard and etc. Smoking also can decrease our immune system. Because of this, our body can easily get cancer, heart disease, stroke, lung diseases, diabetes, chronic and etc. When smoking is allowed in public places like restaurants, shopping malls, public transport, parks, and schools everyone is at risk of exposure to Second-hand smoke. The aim of this project is to deliver the message that is to stop smoking and vaping especially for the new generation.